Evaluation of cracks caused by mechanical vibrations in buildings - Soares, Alvaro Manoel de Souza [UNESP]; Brito, Luiz Antonio Perrone Ferreira de; Gonçalves, João Bosco; Nazari, Bianca Artencio (Springer, 2014)
The problem of cracks in building plays a very important rule in civil engineering and architecture areas. Mechanical vibrations and its effects should be monitored to prevent major damages. This kind of problem affects buildings everywhere but is particularly important if the building belongs to a city that has an historical background and needs preservation. This paper addresses the problem of damages in buildings of a historical Brazilian city, Taubat,, located at So Paulo state. The international reference for a study of the effects of vibration on structures is DIN 4150-3 (1999) Vibration in buildings, in effect structures. The objective of this study is to evaluate the impact-induced vibration due to railway traffic and vehicles at the University Hospital. The results indicate that the boundary of structural integrity is reached but not the noise criterion.
Keywords: Accelerometer; Data acquisition; Digital filtering; Vibration